The Impact of E-Performance Implementation and Work Motivation on Employee Performance: The Role of Technology Acceptance as a Mediator - Suryaningsi Primasari; Trisninawati; Fitriasuri; Dina Mellita (Indonesian Journal of Business Analytics, 2025)
This study aims to analyze the impact of e-performance implementation and work motivation on employee performance with technology acceptance as a mediating variable at the XX Department of XYZ Province. This study discusses issues such as declining employee performance, utilization of new technology, and employees who are 45 years and over. Using a quantitative approach with an explanatory causal design, data were collected from a total of 114 employees through a Google Form-based questionnaire and printed questionnaire sheets. The results indicated that the implementation of e-performance and work motivation significantly influenced technology acceptance, which further impacted employee performance. The implementation of e-performance and work motivation contributed positively to employee performance, with technology acceptance as a key factor in increasing specific areas of productivity. This study highlights the importance of prioritizing the implementation of e-performance and work motivation to enhance employee performance and productivity.